Argumentative Hyperbole as Fallacy - Kreider, A. J. (Informal Logic, 2022)
In typical critical thinking texts, hyperbole is presented as being largely “argumentationally innocent” - it’s primary role being to express emotion of to bring desired emphases to a particular point. This discounts its prevalent use in argumentation, as it is also used as a device to persuade, and in particular, to persuade an interlocutor that they should take or support a course of action. When it is so used, the exaggerated claims would, if true, provide greater support for the conclusion. But since the claims are not fully accurate, this “greater support” is only illusory. Its use is thus deceptive and counts as fallacious reasoning.